Perception of virtual classroom interaction and level of soft skills in college students - Julio Éfrain Postigo Zumarán (Universidade Estadual do Ceará, 2021)
The purpose of this study is to specify the relationship between the perception of classroom interaction and the level of soft skills. A cross-cutting, correlal observational study was conducted on a sample of 507 students from the seventh to tenth cycle of the branch's professional schools in Arequipa from a private Peruvian university, recruited electronically in 2020. The instruments applied were the Virtual Classroom Interaction Perception Scale and the Soft Skills Scale. The results show the existence of a positive weak relationship between the perception of virtual classroom interaction and soft skills. The correlation was .114, the size of the effect is medium, being 0.3376389. In terms of statistical power, the value exceeds 0.80, obtaining the value of 0.950. It is concluded that there is a significant and positive relationship between the variables, even though the relationship between the two variables is weak.